Therapeutic frontiers in viral myocarditis: targeting inflammation, viruses, oxidative stress, and myocardial repair - Xu, Jingyao; Chen, Xuanjia; Guan, Xia; Zhang, Haiying; Liu, Yan; Zhang, Min (Frontiers in Immunology, 2025)
Viral myocarditis (VMC) is a life-threatening inflammatory cardiomyopathy with a global incidence rate of 10–22 per 100,000 people. It is the most common clinical manifestation of myocardial inflammation. Myocardial cell injury and fibrosis are the pathological characteristics of VMC. Coxsackievirus B3 (CVB3), parvovirus B19 (PVB19), Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2), and adenovirus (AdV) are the main causes that induce viral myocarditis. Among them, CVB3 has become the main pathogen, accounting for more than 50% of the confirmed cases of VMC. The clinical manifestations of this disease are extensive, ranging from asymptomatic carriers to sudden cardiac death caused by acute decompensated heart failure and arrhythmia. Current therapeutic strategies for VMC focus on four key approaches: (1) Anti-inflammatory interventions targeting inflammatory cells and mediators; (2) Antiviral therapies employing gene editing, viral protease inhibitors, and RNA polymerase inhibitors; (3) Myocardial protection through tissue repair promotion and nutritional support; (4) Oxidative stress mitigation using antioxidants. This article will systematically summarize the progress of VMC management in recent years and provide personal insights for VMC management.